Virtual Reality and Mixed Reality: 22nd EuroXR International Conference, EuroXR 2025, Winterthur, Switzerland, September 3–5, 2025, Proceedings - (:unkn) unknown (My University, 2025)
This book constitutes the refereed proceedings of the 22nd International Conference on Virtual Reality and Mixed Reality, EuroXR 2025, held in Winterthur, Switzerland, during September 3–5, 2025. The 17 full papers presented were carefully reviewed and selected from 51 submissions. The papers are grouped into the following topics: Rendering and streaming; content synthesis and creation; human factors and perception; and interaction techniques.